Resolving the African Financial Development Gap : Cross-Country Comparisons and a Within-Country Study of Kenya - Allen, Franklin; Carletti, Elena; Cull, Robert; Qian, Jun; Senbet, Lemma; Valenzuela, Patricio (World Bank, Washington, DC, 2013)
With extensive country and firm-level data sets, this paper first documents that the financial sectors of most Sub-Saharan African countries remain significantly underdeveloped by the standards of other developing countries. The paper also finds that population density appears to be considerably more important for banking sector development in Africa than elsewhere. To better understand how countries can overcome the high costs of developing viable banking sectors outside large metropolitan areas, the analysis focuses on Kenya, which has made significant strides in financial inclusion and development in recent years. The paper finds a positive and significant impact of Equity Bank, a leading private commercial bank, on financial access, especially for underprivileged households. Equity Bank's business model -- providing financial services to population segments typically ignored by traditional commercial banks and generating sustainable profits in the process -- can be a potential solution to the financial access problem that has hindered the development of inclusive financial sectors in many other African countries.